2004
DOI: 10.1046/j.1600-6143.2004.00608.x
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Left Ventricular Hypertrophy After Arteriovenous Fistula Closure in Renal Transplant Recipients: A Long-Term Follow-Up

Abstract: The long-term effects of hemodialysis arteriovenous fistula (AVF) closure on left ventricular (LV) morphology are unknown. Using echocardiography, we prospectively studied 17 kidney transplant recipients before, 1, and, 21 months after AVF closure (mean fistula flow 1371 ± 727 mL/min). Eight kidney transplant recipients with a patent AVF, matched for age, time after AVF creation, and time after transplantation, served as controls. LV mass index (LVMI) decreased from 139 ± 44 g/m 2 before AVF closure to 127 ± 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 29 publications
1
59
1
1
Order By: Relevance
“…Many studies have demonstrated that this hypercirculation can contribute to LVH, [26] while surgical closure of the arteriovenous fistula has been shown to reduce LVH in kidney transplant recipients. [27,28] Comparing Asian and European dialysis patients, it has been suggested that the survival of dialysis patients may differ among different races. [29,30] Both registry data and data from Asian countries demonstrated a higher patient survival rate in oriental Asians on PD than in western PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that this hypercirculation can contribute to LVH, [26] while surgical closure of the arteriovenous fistula has been shown to reduce LVH in kidney transplant recipients. [27,28] Comparing Asian and European dialysis patients, it has been suggested that the survival of dialysis patients may differ among different races. [29,30] Both registry data and data from Asian countries demonstrated a higher patient survival rate in oriental Asians on PD than in western PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Concentric remodeling means left ventricular remodeling without increasing mass. As shown by Unger et al [11], left ventricular morphology type partially depends on whether the patient has an active arteriovenous shunt. However, further studies on left ventricular morphology in RT recipients would be useful for understanding the mechanisms responsible for it and instituting the appropriate treatment.…”
Section: Discussionmentioning
confidence: 91%
“…A study of 20 transplanted patients, 4 months after closure of the Avf, observed reduction of the Lv diastolic diameter and mass index, although the intensity of the Avf flow before the occlusion did not have an impact on the improvement of these parameters. 45 Unger et al, 46 in a 21-month follow-up study after Avf closure, also demonstrated a significant reduction of the Lv mass index, although with an increase of the relative thickness. this increased relative thickness, however, might be accounted for by a more marked reduction of the enddiastolic diameter than of the wall thickness.…”
Section: Role Of Doppler Echocardiographymentioning
confidence: 88%